The Possibilities of Applying Ultrasound-Guided Percutaneous Electrolysis For Musculoskeletal Pain - Trajkov, Marija T; Stevanović, Kristina; Kljajić, Dragana; Šimpraga, Ljiljana; Ilić, Milan; Stojković, Ivan (PONS - medicinski časopis, 2024)
Physical therapy is constantly evolving and adapting to new information and technologies in order to provide optimal care to patients with various musculoskeletal conditions. In this context, recent advances in technology and therapy methods has led to the introduction of new techniques, among which ultrasound-guided percutaneous electrolysis stands out. This technique, which combines the principle of electrotherapy (direct current) with percutaneous needle application, is becoming increasingly significant in the rehabilitation of patients with tendinopathies, myofascial pain syndromes, and other musculoskeletal conditions. The largest number of studies to date indicate its effectiveness, whether it is applied as an individual procedure, or in combination with other physical modalities and therapeutic exercises. The therapeutic effects were monitored in both the short and long term. The most adequate therapeutic protocols are still being sought after, considering that this technique has recently been introduced as a way of decreasing the symptoms and consequences of musculoskeletal pain. The aim of this research was to review the approaches and therapeutic protocols for the application of percutaneous electrolysis in the treatment of musculoskeletal pain. The research results indicate positive therapeutic effects, as well as the advantages of applying ultrasound-guided percutaneous electrolysis for musculoskeletal pain.